Physical and Psychological Health Problems in the Elderly - Rosdiana, Ika; Hapsari, Dewi Putri; Aisyah, Nurmalita; Utami, Adelia Yunika; Alvenia, Mia (Journal of Advanced Multidisciplinary Research, 2024)
Population Aging is a global phenomenon—almost every country in the world. With increasing age, there will also be an increase in various morbidity patterns in the elderly population. This study aims to determine the physical and psychological problems in the elderly and the factors related to the health problems of the elderly and appropriate interventions. The research method is descriptive with observational analytics using physical and psychological assessment tools. The measurement tools used were fall risk, cognitive impairment, sleep quality, insomnia, activities of daily living, joint pain, anxiety disorders and quality of life in the elderly. The number of respondents is 30 elderly who live in nursing homes and the technique used is interviews. The results of this study were 76.7% had a low risk of falling, 80% had no cognitive impairment, 73.33% had good sleep quality with a global value of 5.83, 46.67% had insomnia, 50% had anxiety disorders, 50% had independent activities, 66.67% had joint pain mild, and in general 83.33% quality of life is good. In conclusion, most of the respondents did not experience physical and psychological disorders, but most of the elderly experienced moderate joint pain and half of the respondents needed assistance to carry out their daily activities. Thus, it is necessary to have interventions that are in accordance with the needs of the elderly in nursing homes.